Tuning transcription of nutrient utilization genes to catabolic rate promotes growth in a gut bacterium. Issue 5 (12th August 2014) - Raghavan, Varsha; Lowe, Elisabeth C.; Townsend, Guy E.; Bolam, David N.; Groisman, Eduardo A.
Summary Cells respond to nutrient availability by expressing nutrient catabolic genes. We report that the regulator controlling utilization of chondroitin sulphate (CS) in the mammalian gut symbiont Bacteroides thetaiotaomicron is activated by an intermediate in CS breakdown rather than CS itself. We determine that the rate‐determining enzyme in CS breakdown is responsible for degrading this intermediate and establish that the levels of the enzyme increase 100‐fold, whereas those of the regulator remain constant upon exposure to CS. Because enzyme and regulator compete for the intermediate, B. thetaiotaomicron tunes transcription of CS utilization genes to CS catabolic rate. This tuning results in a transient increase in CS utilization transcripts upon exposure to excess CS. Constitutive expression of the rate‐determining enzyme hindered activation of CS utilization genes and growth on CS. An analogous mechanism regulates heparin utilization genes, suggesting that the identified strategy aids B. thetaiotaomicron in the competitive gut environment.